2012
DOI: 10.1590/s0100-879x2012007500079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of renal function in sickle cell disease patients in Brazil

Abstract: The objective of this study was to investigate renal function in a cohort of 98 patients with sickle cell disease (SCD) followed up at a tertiary hospital in Brazil. Clinical and laboratory characteristics at the time of the most recent medical examination were analyzed. Renal function was evaluated by the estimation of glomerular filtration rate (GFR) by the criteria of the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI). We compared patients with normal GFR to patients with decreased GFR (<60 mL·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
1
6
2
Order By: Relevance
“…In a cohort of 85 children with SCD, 76% had glomerular hyperfiltration [15]. In a recent study performed in our region, hyperfiltration was found in 53% of SCD patients [12], which was higher than the found in the present study.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In a cohort of 85 children with SCD, 76% had glomerular hyperfiltration [15]. In a recent study performed in our region, hyperfiltration was found in 53% of SCD patients [12], which was higher than the found in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…In the present study, there was no difference in the mean glomerular filtration rate (GFR) between patients and controls, however there was a significant number of SCD patients with decreased GFR (<60mL/min/1.73m 2 ), which was found in 11.5% of cases, which is higher than the previous found in another study in our region, which found a prevalence of GFR<60mL/min/1.73m 2 in 5.1% of SCD patients [12]. We have identified 3 patients with renal failure, probably corresponding to chronic kidney disease, and all these 3 patients had concentration and acidification deficit.…”
Section: Discussionmentioning
confidence: 56%
“…It was also found that approximately half of the patients (43.2%) were taking hydroxyurea. This percentage is higher than that reported by other studies conducted in Brazil 18,22 and the USA, 23,24 and demonstrates good adherence of the patients to treatment and the healthcare team's confidence in the efficacy of the medicine. However, only 11% of under 5-year-old children were taking hydroxyurea, which seems to reflect the concerns about the overall safety of this medicine, mainly in very young children.…”
Section: Discussioncontrasting
confidence: 60%
“…[10],all of which would lead to distorted levels of serum creatinine and creatinine clearance measurements in urine as well as lead to invalidating current methods to determine renal dysfunction, these methods are being widely used in assessing kidney function in SCD [19], [20], [21], [22], [23], [24], [25]. These studies have included children and adults and have utilized various predictive equations such as MDRD, CG, Schwartz, and CKD-EPI to estimate GFR as a marker of renal function in these studies.…”
Section: Discussionmentioning
confidence: 99%